How Effective Are Computer-Assisted Pronunciation and YouTube-Based Instructions in Improving Oral English Proficiency Among Secondary School Students? - Olufunke Olatoye; Oluwakemi Olurinola (WISE Pendidikan Indonesia, 2026)
This study investigates the effectiveness of Computer-Assisted Pronunciation Instruction (CAPI) and YouTube-based instruction in enhancing oral English proficiency among Nigerian senior secondary school students. A quasi-experimental design was employed, involving three groups: the CAPI group, the YouTube group, and a control group. The study utilized an Oral English Language Proficiency Test (OELPT), administered before and after the treatments, to assess students' pronunciation improvements. Data were analyzed using Analysis of Covariance (ANCOVA) to determine the main and interaction effects of the treatment, gender, and language spoken at home. The results revealed a significant effect of the treatment on students' oral proficiency (F = 14.530, p < 0.05), with both CAPI and YouTube-based instruction outperforming the control group. However, gender and language spoken at home did not significantly influence the outcomes (p > 0.05). There were also no significant interaction effects between treatment and these demographic factors, suggesting that the treatments were equally effective for both male and female students and regardless of the language spoken at home. These findings highlight the effectiveness of CAPI and YouTube as technology-based tools for improving oral English proficiency, with implications for language instruction in diverse educational contexts. This study contributes to the growing body of research on technology-enhanced language learning, providing evidence of the efficacy of CAPI and YouTube-based instruction in secondary school settings, particularly in resource-constrained environments. The findings suggest that integrating digital tools into language education can offer a scalable, accessible solution to improving students' oral proficiency, regardless of their socio-demographic backgrounds.